AB0045 Plasma and Tissue Expression of PTX3 in Patients with Chronic Periaortitis. (10th June 2014) - Ramirez, G.A.; Tombetti, E.; Baldini, M.; Bottazzi, B.; Buzio, C.; Dell'Antonio, G.; Monno, A.; Nicastro, M.; Urban, M.L.; Rovere-Querini, P.; Sabbadini, M.G.; Mantovani, A.; et al.
Abstract : Background: Chronic Periaortitis (CP) is a rare fibro-inflammatory disorder of unknown etiology, lying at the crossroads between large vessel vasculitides (LVV) and fibrosing diseases [1]. LVV-like pathogenic features are probably responsible for medial and adventitial inflammation of the aortic wall [2], whereas Th2-driven eosinophilic and B-cell responses are thought to account for the development of fibrosis of the adjacent peritoneum [1]. PTX3 is a soluble innate pattern recognition receptor of the pentraxin family, generated and released on demand at sites of inflammation. PTX3 is involved in ancestral defensive responses, processing of cell debris and autoantigens and regulation of tissue remodeling and cell recruitment [3]. Objectives: The identification of a potential role of PTX3 in regulating the outcome of vessel inflammation and of its selective expression at sites of vessel injury in small and large vessel vasculitides prompted us to investigate its involvement in patients with CP. Methods: PTX3 expression was assessed by immunohistochemistry on tissue samples of periaortic tissue from five patients with CP. PTX3 systemic concentration was assessed in plasma samples of 14 CP patients and 20 healthy controls. Results: PTX3 was consistently expressed at high levels by leukocytes infiltrating the periaortic tissue of patients with CP. In contrast, a relatively restricted association with the extracellular matrix has been observed, which is an hallmark of several inflammatory conditions associated with vessel and tissue remodeling. Moreover, systemic levels of the protein do not apparently reflect the substantial expression of the protein in the retroperitoneal tissue. Conclusions: PTX3 is expressed at sites of inflammation and tissue remodeling in patients with CP. Larger studies are required to confirm histological data and assess possible pathogenic roles of PTX3 in modulating cell recruitment and tissue remodeling. Serological data should also be replicated in larger cohorts of patients and appropriate controls. References: Pipitone N, et al., Best Pract Res Clin Rheumatol, 2012 Ramshaw AL, et al., J Clin Pathol, 1994 Manfredi AA, et al., Curr Opin Immunol, 2008 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3387